2022
DOI: 10.1186/s12917-022-03446-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell composition of the bronchoalveolar lavage fluid in healthy and respiratory diseased dromedary camels

Abstract: Background Respiratory diseases are among the most common and expensive to treat diseases in camels with a great economic impact on camel health, welfare, and production. Bronchoalveolar lavage fluid (BALF) has been proven as a valuable sample for investigating the leukocyte populations in the respiratory tract of several species. In the present study, fluorescent antibody labeling and flow cytometry were used to study the immune cell composition of BALF in dromedary camels. Animals with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…BALF samples are also useful in giving insight into the severity and stage of inflammatory reactions in the lung and in the detection of subclinical pulmonary diseases ( Van Driessche et al ., 2019 ; Shawaf et al ., 2021 ; Kang et al ., 2022 ). Recently, two studies reported the percentage of cytological BALF in dromedary camels with and without respiratory diseases ( Shawaf et al ., 2021 , 2022 ). However, several previous studies on different animal species indicated the effect of the season, gender, and age on the percentage of cells in the BALF samples ( Pacheco et al ., 2014 ; Secombe et al ., 2015 ; Hostetter et al ., 2017 ; Davis and Sheats, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…BALF samples are also useful in giving insight into the severity and stage of inflammatory reactions in the lung and in the detection of subclinical pulmonary diseases ( Van Driessche et al ., 2019 ; Shawaf et al ., 2021 ; Kang et al ., 2022 ). Recently, two studies reported the percentage of cytological BALF in dromedary camels with and without respiratory diseases ( Shawaf et al ., 2021 , 2022 ). However, several previous studies on different animal species indicated the effect of the season, gender, and age on the percentage of cells in the BALF samples ( Pacheco et al ., 2014 ; Secombe et al ., 2015 ; Hostetter et al ., 2017 ; Davis and Sheats, 2019 ).…”
Section: Introductionmentioning
confidence: 99%